Modelling Wages and Prices for the Smaller OECD Countries - Kawasaki, Kenichi (OECD Economics Department Working Papers, 1990)
This paper presents work on wage/price blocks for the smaller OECD countries which has been implemented in OECD's world econometric model, INTERLINK. The paper discusses theoretical, statistical and practical aspects of the estimation of business sector wage equations and five domestic demand deflators. It also presents a variety of diagnostic simulations in order to evaluate overall model properties ...